2017
DOI: 10.1016/j.metabol.2017.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K and osteoporosis: Myth or reality?

Abstract: Vitamin K is a liposoluble vitamin. The predominant dietary form, phylloquinone or vitamin K1, is found in plants and green vegetables; whereas menaquinone, or vitamin K2, is endogenously synthesized by intestinal bacteria and includes several subtypes that differ in side chain length. Aside from its established role in blood clotting, several studies now support a critical function of vitamin K in improving bone health. Vitamin K is in fact required for osteocalcin carboxylation that in turn regulates bone mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
85
1
8

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 97 publications
0
85
1
8
Order By: Relevance
“…However, little was known about the functions of the top four metabolites (Table 1) and their roles on bone metabolism warrants further functional analysis. On the other hand, our analysis did not detect several metabolites that were previously known to be causally associated with BMD, such as vitamin K (Palermo et al 2017). This is mainly because that some of these metabolites (e.g., vitamin K) were not included in the metabolomics GWAS dataset (Shin et al 2014).…”
Section: Discussioncontrasting
confidence: 78%
“…However, little was known about the functions of the top four metabolites (Table 1) and their roles on bone metabolism warrants further functional analysis. On the other hand, our analysis did not detect several metabolites that were previously known to be causally associated with BMD, such as vitamin K (Palermo et al 2017). This is mainly because that some of these metabolites (e.g., vitamin K) were not included in the metabolomics GWAS dataset (Shin et al 2014).…”
Section: Discussioncontrasting
confidence: 78%
“…Finally, the status of vitamin K was not measured directly, because vitamin K is a soluble vitamin with many isoforms, and vitamin K plasma value alone is not sufficient to assess its real status. 27 In conclusion, bone quality markers did not change significantly after ADT. Whereas, it was confirmed that BMD decreased significantly after ADT.…”
Section: Discussionmentioning
confidence: 77%
“…SXR stimulates proteins, such as tsukushin and matrilin‐2, which are associated with collagens to promote collagen‐accumulation in osteoblastic cells . A prospective study reported the efficacy of vitamin K supplementation for BMD and bone fractures . In a randomized trial carried out by Knapen et al ., for 3 years healthy postmenopausal women received a placebo or vitamin K2 supplements, menaquinone‐7 (MK‐7, 180 μg/day).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations